Solar thermochemical ZnO/ZnSO4 water splitting cycle for hydrogen production. (14th September 2017) - Bhosale, Rahul; Kumar, Anand; AlMomani, Fares; Gupta, Ram B.
Abstract: In this paper, solar reactor efficiency analysis of the solar thermochemical two-step zinc oxide–zinc sulfate (ZnO–ZnSO4 ) water splitting cycle. In step-1, the ZnSO4 is thermally decomposed into ZnO, SO2, and O2 using solar energy input. In step-2, the ZnO is re-oxidized into ZnSO4 via water splitting reaction producing H2 . The ZnSO4 is recycled back to the solar reactor and hence can be re-used in multiple cycles. The equilibrium compositions associated with the thermal reduction and water-splitting steps are identified by performing HSC simulations. The effect of Ar towards decreasing the required thermal reduction temperature is also explored. The total solar energy input and the re-radiation losses from the ZnO–ZnSO4 water splitting cycle are estimated. Likewise, the amount of heat energy released by different coolers and water splitting reactor is also determined. Thermodynamic calculations indicate that the cycle ( η cycle ) and solar-to-fuel energy conversion efficiency ( η solar - to - fuel ) of the ZnO–ZnSO4 water splitting cycle are equal to 40.6% and 48.9% (without heat recuperation). These efficiency values are higher than previously investigated thermochemical water splitting cycles and can be increased further by employing heat recuperation. Highlights: Thermal reduction of ZnSO4 is feasible above 1270 K. H2 production via water splitting reaction is possible below 395 K. Q ˙ s o l a r - c y c l e increases with the decrease in T H . Efficiency values obtained are significantly higher than previous cycles. Efficiency values increases due to heat recuperation.